Perancangan Sistem Informasi Kepegawaian Pada PT. Bakri Karya Sarana Batam - Zuli Astari; Desi Pibriana; Rusbandi Rusbandi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
PT Bakri Karya Sarana is a company which focused on service providers or outsourcing. In the process of managing its employee data, PT Bakri Karya Sarana still has several obstacles, such as the new employees reqruitments, employee attendance, permit data, leave, mutation, promotion, demotion, resignation, employee warning letters, field staff appraisal and quality assessment from clients. The purpose of this research is to design and create a website-based personnel information system at PT Bakri Karya Sarana. The methodology used in this research is an iterative methodology consisting of planning, problem analysis, design, implementation and maintenance. With this design information system, it can help and simplify HRD performance in managing employees data starting from the process of recruiting new employees, employee attendance, permit data, leave, mutation, promotion, demotion, resignation, employee warning letters, field employee assessment , assessment of the quality of the client and all reports can be received by the director quickly and accurately.